Androgen receptor and ultrastructural features of Nigella sativa oil and nicotine-treated male rat reproductive glands - Lina S.,; Eliza H.,; Hashida N.H.,; Ibrahim S.F.,; Osman K., (Penerbit Universiti Kebangsaan Malaysia, 2018)
Nicotine is claimed to increase free radicals, DNA damage and lipid peroxidation in male reproductive organs. Nigella sativa has been identified to ameliorate these adverse effects due to nicotine intake. This study was conducted to evaluate potential protective effects of N. sativa oil on the adverse effects of nicotine on androgen receptors (AR) and ultrastructural features of rat seminal vesicles and prostate glands. Twenty four Sprague Dawley male rats, 7-9 weeks of age and 200-250 g body weight (BW) were randomly divided into; Group 1 Saline (S), forced fed with 0.1 mL/100 g BW of 0.9% normal saline; Group 2 Nicotine (N), intramuscularly injected with 0.5 mg/100 g BW of nicotine; Group 3 N. sativa (NS), forced fed with 6.0 μL/100 g BW of N. sativa and Group 4 Nicotine-N. sativa (NNS), co-administered with 0.5 mg/100 g BW of nicotine and 6.0 μL/100 g BW of N. sativa. The seminal vesicles and prostate glands were extracted after 100 days of treatment. The seminal vesicle and prostate gland were processed for ultrastructural study and androgen receptor detection. The epithelial cells in prostate gland and seminal vesicle of the N group showed weaker brown staining intensity as compared to that of in the NS and NNS groups. This was consistent with the presence of some ultracellular changes observed in the prostate gland and seminal vesicle tissues of the N group. Findings from this study suggested that administration of N. sativa results in ameliorating effects on both the prostate gland and seminal vesicle structures and functions of the nicotine-treated rats.